2023
DOI: 10.1111/jdv.18916
|View full text |Cite
|
Sign up to set email alerts
|

The journey of patients with skin diseases from the first consultation to the diagnosis in a representative sample of the European general population from the EADV burden of skin diseases study

Marie Aleth Richard,
Carle Paul,
Tamar Nijsten
et al.

Abstract: BackgroundThe journey of patients with skin diseases through healthcare has been scarcely investigated.ObjectiveTo analyse the journey of people with skin diseases in the different healthcare environment in Europe.MethodsThis multinational, cross‐sectional, European study was conducted on a representative sample of the adult general population of 27 European countries. The prevalence of the most frequent skin diseases was determined. Information was collected on the patient journey from the first medical consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Dear Editor, It is with great interest that we read Bootsma et al's 1 response to our article 'The journey of patients with skin diseases from the first consultation to the diagnosis in a representative sample of the European general population from the EADV burden of skin diseases study'. 2 In our study on 44,689 individuals from 27 European countries, 3574 (8%) reported having alopecia (all types). Among them, 44.7% did not consult a healthcare professional, of which 53.7% said that it wasn't worrying enough for them to consult.…”
mentioning
confidence: 56%
“…Dear Editor, It is with great interest that we read Bootsma et al's 1 response to our article 'The journey of patients with skin diseases from the first consultation to the diagnosis in a representative sample of the European general population from the EADV burden of skin diseases study'. 2 In our study on 44,689 individuals from 27 European countries, 3574 (8%) reported having alopecia (all types). Among them, 44.7% did not consult a healthcare professional, of which 53.7% said that it wasn't worrying enough for them to consult.…”
mentioning
confidence: 56%
“…Additionally, individuals with dermatological conditions tend to minimize or postpone seeking care for symptoms that, while not deemed medically urgent, can significantly affect their emotional and psychological well-being . Furthermore, given the tendency for individuals to self-treat common dermatological conditions such as acne or fungal infections, it is plausible that a similar approach is taken with seborrheic dermatitis, despite evidence linking such practices to worse dermatological outcomes …”
Section: Discussionmentioning
confidence: 99%
“…However, despite the high incidence of fungal skin diseases, they are often overshadowed by more prominent communicable diseases, such as HIV/AIDS, tuberculosis, and invasive fungal infections 6 . In the realm of global health research, this trend is especially evident, as the focus largely remains on developed nations, frequently overlooking the more critical fungal infection challenges prevalent in low‐ and middle‐income countries 7–9 . In these countries, the number of skin fungal diseases may be severely underestimated 10,11 …”
Section: Introductionmentioning
confidence: 99%